Analysis of ClC-2 channels as an alternative pathway for chloride conduction in cystic fibrosis airway cells - Schwiebert, Erik M. (The National Academy of Sciences, 1998)
Cystic fibrosis (CF) is a lethal inherited disease that results from abnormal chloride conduction in epithelial tissues. ClC-2 chloride channels are expressed in epithelia affected by CF and may provide a key “alternative” target for pharmacotherapy of this disease. To explore this possibility, the expression level of ClC-2 channels was genetically manipulated in airway epithelial cells derived from a cystic fibrosis patient (IB3-1). Whole-cell patch-clamp analysis of cells overexpressing ClC-2 identified hyperpolarization-activated Cl(−) currents (HACCs) that displayed time- and voltage-dependent activation, and an inwardly rectifying steady-state current–voltage relationship. Reduction of extracellular pH to 5.0 caused significant increases in HACCs in overexpressing cells, and the appearance of robust currents in parental IB3-1 cells. IB3-1 cells stably transfected with the antisense ClC-2 cDNA showed reduced expression of ClC-2 compared with parental cells by Western blotting, and a significant reduction in the magnitude of pH-dependent HACCs. To determine whether changes in extracellular pH alone could initiate chloride transport via ClC-2 channels, we performed (36)Cl(−) efflux studies on overexpressing cells and cells with endogenous expression of ClC-2. Acidic extracellular pH increased (36)Cl(−) efflux rates in both cell types, although the ClC-2 overexpressing cells had significantly greater chloride conduction and a longer duration of efflux than the parental cells. Compounds that exploit the pH mechanism of activating endogenous ClC-2 channels may provide a pharmacologic option for increasing chloride conductance in the airways of CF patients.